2013
DOI: 10.1007/s00497-012-0209-0
|View full text |Cite
|
Sign up to set email alerts
|

Volume-based pollen size analysis: an advanced method to assess somatic and gametophytic ploidy in flowering plants

Abstract: Pollen size is often used as a biological parameter to estimate the ploidy and viability of mature pollen grains. In general, pollen size quantification is performed one- or two-dimensionally using image-based diameter measurements. As these approaches are elaborate and time consuming, alternative approaches that enable a quick, reliable analysis of pollen size are highly relevant for plant research. In this study, we present the volume-based particle size analysis technique as an alternative method to charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 69 publications
2
47
1
Order By: Relevance
“…Partly, this is because the upper and lower tails of each subpopulation can overlap with one another. Such overlap has been observed in studies of pollen diameter from polyploid Arabidopsis plants, in which the right-hand tail of pollen from triploid (3n) plants overlaps with the left-hand tail of pollen from hexaploid (6n) plants [22]. Such overlap in the diameter of pollen from polyploids can be shown clearly in studies of modern plants because the ploidy of the parent plant is known.…”
Section: (B) Classopollis Pollen Size Analysismentioning
confidence: 71%
See 2 more Smart Citations
“…Partly, this is because the upper and lower tails of each subpopulation can overlap with one another. Such overlap has been observed in studies of pollen diameter from polyploid Arabidopsis plants, in which the right-hand tail of pollen from triploid (3n) plants overlaps with the left-hand tail of pollen from hexaploid (6n) plants [22]. Such overlap in the diameter of pollen from polyploids can be shown clearly in studies of modern plants because the ploidy of the parent plant is known.…”
Section: (B) Classopollis Pollen Size Analysismentioning
confidence: 71%
“…Principally, the observed pattern can be ascribed to the formation of anucleate, haploid and unreduced 2n pollen. In modern plants, pollen size is related to the number of chromosomes with increasing pollen volume at higher ploidy levels [9,[19][20][21][22][32][33][34][35]. While the number of pollen openings has been reported to vary in some polyploidy angiosperms [36], in this study, the number of pores and the furrows of Classopollis remains constant.…”
Section: (B) Classopollis Pollen Size Analysismentioning
confidence: 75%
See 1 more Smart Citation
“…Analysis showed that pollen grain size discriminated trees into different genetic and ecological groups, suggesting genetics influenced pollen size (Derridj et al 1991). The genetic control on pollen size may stem from genome size (Bennett 1972;De Storme et al 2013), in particular the effect of an increased number of chromosomes due to polyploidy (Kapadia & Gould 1964;Dyer et al 2013). Knight et al (2010) found a significant positive trend between pollen width and genome size across 464 species.…”
mentioning
confidence: 91%
“…Grain size may be studied to improve the taxonomic resolution of pollen identification, for example with Pinus pollen (Desprat et al 2015), Poaceae pollen (Radaeski et al 2016), and indeed with Cedrus pollen (Fujiki et al 2003). Pollen size has also been correlated with genome size and may indicate polyploidy (three or more chromosome sets) in plants (Gould 1957;Kapadia & Gould 1964;Bennett 1972;Tate et al 2005;Knight et al 2010;De Storme et al 2013). Increasingly, geochemical studies utilising pollen, such as stable isotope analysis for palaeoclimate reconstructions (Amundson et al 1997;Loader & Hemming 2004;Nelson et al 2006Nelson et al , 2007King et al 2012;Nelson 2012;Bell et al 2017) and biomarker analysis for UV-B reconstructions (Rozema et al 2001(Rozema et al , 2002Fraser et al 2011;Willis et al 2011;Lomax et al 2012;, require detailed knowledge of grain size for developing techniques to isolate specific grains from fossil assemblages.…”
Section: Introductionmentioning
confidence: 99%